The Rise of The Gig Economy and Its Impact on HRM Research: a Dynamic Bibliometric Analysis - Nayoan Baskautshar; Mimi Kurnia Nengsih (Journal of Economics and Management Scienties, 2026)
This study conducts a dynamic bibliometric analysis of 2,695 articles to map the evolution, structure, and research trends at the intersection of the gig economy and human resource management (HRM) from 2010 to 2024. Using VOSviewer to analyse Scopus-indexed literature, the research identifies the geographic dominance of the United States and the United Kingdom in publication output. At the same time, countries such as the Netherlands and Singapore demonstrate higher impact per article. A keyword co-occurrence analysis reveals the consolidation of the research field around three major, yet poorly integrated, thematic clusters: regulation, worker psychological Well-being, and technology governance. Bibliographic coupling analysis of authors and institutional collaboration confirms fragmentation within the intellectual community, with collaboration patterns centred on universities in the Global North. These findings underscore the need for a future research agenda that is more geographically inclusive, integrative across paradigms, and focused on connecting technology analysis with policy implications and social protection for gig workers. The contribution of this study is an evidence-based intellectual map that can guide the Development of more adaptive HRM theory and practice in the gig economy era.